Helena Solberg: trajetória de uma documentarista brasileira - Mariana Ribeiro da Silva Tavares (2011)
This thesis discusses the documentary films of the Brazilian filmmaker Helena Solberg, consisting of twelve documentaries produced in the United States and in Brazil in the last 47 years. We have identified several different phases of the filmmakers career Cinema Novo; The Women Trilogy, the Political Phase, and the Enchantment with the power of words in her current phase, in an effort to demonstrate that Helena Solberg has a singular and coherent body of work in the context of Brazilian documentary production and that she remains faithful to the thematic and stylistic elements that inform her directorial universe without losingsight of the transformations in documentary film language and international tendencies in the last five decades. This study aims to fill the gap in terms of references to her work and career in the bibliography of Brazilian documentary filmmaking, and identify the stylistic and thematic elements that inform her creative universe.